Integrating competition policy and innovation policy: the case of R&D cooperation - Georg von Graevenitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
I develop a model of R&D cooperation with uncertain research outcomes. In this model asymmetric outcomes of R&D competition emerge naturally. Therefore ex-ante and ex-post R&D cooperation can be studied as alternatives for firms. Using this model I compare welfare losses under ex-ante and ex-post R&D cooperation as the degree of product market competition varies. It emerges that the relative size of these welfare losses is monotonically related to the degree of product market competition and the degree of technological opportunity. The implications of these results for the interaction of competition policy and innovation policy are discussed.
urn:nbn:de:bvb:19-epub-13513-9
Keywords: 330